2018
DOI: 10.1002/glia.23462
|View full text |Cite
|
Sign up to set email alerts
|

Nogo‐A inhibits vascular regeneration in ischemic retinopathy

Abstract: Nogo-A is a potent glial-derived inhibitor of axon growth in the injured CNS and acts as a negative regulator of developmental angiogenesis by inhibiting vascular endothelial cell migration. However, its function in pathological angiogenesis has never been studied after ischemic injury in the CNS. Using the mouse model of oxygen-induced retinopathy (OIR) which yields defined zones of retinal ischemia, our goal was to investigate the role of Nogo-A in vascular regeneration. We demonstrate a marked upregulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 62 publications
2
13
0
Order By: Relevance
“…The involvement of Nogo-A in pathological mechanisms affecting the retina suggests that Nogo-A-targeting antibodies may also improve vision in ocular diseases. Our recent results revealed that blocking Nogo-A-Delta 20 with intravitreal injection of 11C7 antibody dramatically increased vascular repair and neuronal function in the retina of mice subjected to ischemic retinopathy 28 . In adult mice, we also reported that Nogo-A KO mice had better visual recovery after retinal injury than WT animals 29 .…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…The involvement of Nogo-A in pathological mechanisms affecting the retina suggests that Nogo-A-targeting antibodies may also improve vision in ocular diseases. Our recent results revealed that blocking Nogo-A-Delta 20 with intravitreal injection of 11C7 antibody dramatically increased vascular repair and neuronal function in the retina of mice subjected to ischemic retinopathy 28 . In adult mice, we also reported that Nogo-A KO mice had better visual recovery after retinal injury than WT animals 29 .…”
Section: Introductionmentioning
confidence: 92%
“…A Ganzfeld system (Phoenix Research Labs, Pleasanton, CA, USA) was used to record photopic ERGs in mice (5-9/group) anesthetized with a ketamine/xylazine mixture, as described before 28,38 . Prior to recording, a drop of 1% Mydriacyl Tropicamide was applied on the cornea for pupil dilation.…”
Section: Electroretinogram (Erg) Recordingmentioning
confidence: 99%
See 3 more Smart Citations